Land and Building Tax Compliance: Administrative Sanctions, Attitudes of Nationalism with Income Levels as Moderator - Sri Lestari Yuli Prastyatini; Latifah Nur Mufidatunnisa (Jurnal Akuntansi dan Perpajakan, 2023)
The realization of tax revenue in Bantul Regency is still below the stipulated value of tax revenue for 2017-2021 which has resulted in not achieving the predetermined tax revenue target. For this reason, the purpose of this study was to determine a level of income as a moderator of the effect of administrative sanctions and nationalism on the compliance of a land and building taxpayer. Source of data used is primary data. The population used is land and building tax payers in the District of Bantul. The research sample used was 124 taxpayers to 122 land and building taxpayers in Bantul District because there were outlier data. Determining the number of samples by snowball sampling technique was used in this study. The data analysis used multiple linear analysis, and hypothesis testing. The results show that administrative sanctions and nationalism have a positive effect on the compliance of a land and building taxpayer. The level of income is not able to moderate administrative sanctions and attitudes of nationalism towards the compliance of a land and building taxpayer